2003
DOI: 10.1562/0031-8655(2003)077<0210:teopal>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photoperiod and Light Irradiance on the Antioxidant Circadian System of Two Species of Crayfish from Different Latitudes: Procambarus clarkii and P. digueti¶

Abstract: This work was carried out to study the antioxidant circadian system of two species of crayfish of different latitude origin. We investigated (1) whether both species possess glutathione circadian rhythms and (2) whether both species' rhythms differ in their ability to synchronize to 24 h cycles. Two batches of Procambarus clarkii and P. digueti were kept in (1) light-dark (LD) 12:12 low irradiance (LI) cycles and then exposed to (2) 72 h of complete darkness, (3) LD 12:12 high irradiance (HI), (4) LD 20:4 LI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
3
11
1
1
Order By: Relevance
“…After 3 days of darkness, the phase relationship increased to w LPO-Glu about 12 h in both. On comparing these values with those obtained in midgut in a previous work (11) (Fig. 6c), GSH-system behavior in the midgut under DD appears to be more similar to OL-B than to retina.…”
Section: Internal Synchrony Between Rhythmssupporting
confidence: 71%
See 1 more Smart Citation
“…After 3 days of darkness, the phase relationship increased to w LPO-Glu about 12 h in both. On comparing these values with those obtained in midgut in a previous work (11) (Fig. 6c), GSH-system behavior in the midgut under DD appears to be more similar to OL-B than to retina.…”
Section: Internal Synchrony Between Rhythmssupporting
confidence: 71%
“…Our results indicate an apparent strikingly direct effect of light on these rhythms that especially in the retina increase their amplitude greatly under 24 h LD cycles, exhibiting a greater than three-fold GSH increment. This is a larger increase than that found in the brain in this work, and in midgut and hemolymph previously (11). The cyclic luminous condition appears to stimulate the entire GSH system in retina as a response to antagonize the oxidative effect of light on this organ.…”
Section: Discussioncontrasting
confidence: 59%
“…Although we did not measure the HIF-1a circadian variations in the current study, the differences between the HIF-1a abundance at 08:00 and 20:00 under all of the experimental conditions (although the differences were not statistically significant because of the high standard errors), and particularly under DD, suggest an HIF-1a circadian rhythm in the central oscillators of crayfish. Interestingly, the relative abundances were similar in the nervous system and retina and reversed under the 20:4 LD condition, which has been reported for other crayfish rhythms under both natural and experimental conditions (2,25). The inverse relationship between the relative abundance of the HIF-1a and HSP70 that was found in the retina, but not in the OL-B complex, under all of the experimental conditions indicates the cross-regulation of both peptides, which has been proposed elsewhere (10).…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies, we demonstrated that the liver in crayfish possess an antioxidant circadian system, as demonstrated by robust GSH circadian rhythms that persist even when the animal is subjected to extreme latitudinal daily cycles (20 h photoperiod). These rhythms were able to acclimate to 20:4 LD light-day cycles and reset to lights on or off, which suggests strong coupling between the central oscillators (eyestalk and brain) and a possible peripheral oscillator in the liver (2).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation